Luminescent Materials: Cation–Anion Interaction‐Directed Molecular Design Strategy for Mechanochromic Luminescence (Adv. Funct. Mater. 6/2014). (February 2014) - Li, Gaocan; Song, Feijie; Wu, Di; Lan, Jingbo; Liu, Xingyan; Wu, Jie; Yang, Shuaijun; Xiao, Dan; You, Jingsong
<x xml:space="preserve">Abstract</x> A series of common N‐heteroaromatic onium fluorophores with striking reversible mechanochromic luminescence are designed and synthesized on page 747 based on a cation–anion interactiondirected molecular design strategy, which has great potential for a wide variety of applications such as sensors, memory devices, motion systems, security systems, rewritable optical media, etc. The image by J. You and co‐workers illustrates how color printing could be realized without ink through the adoption of their mechanochromic materials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>